Indigenous nationals, Canadian citizens : from first contact to Canada 150 and beyond - Courchene, Thomas J. (Montreal ; Ithaca : School of Policy Studies, Queen's University : McGill-Queen's University Press, 2018)
"Indigenous Nationals/Canadian Citizens begins with a detailed policy history from first contact to the Sesquicentennial with major emphasis on the evolution of Canadian policy initiatives relating to Indigenous peoples. This is followed by a focus on the key Supreme Court decisions that have dramatically enhanced Indigenous peoples' legal and constitutional rights. Attention is then directed to the Truth and Reconciliation Commission and the associated 'Calls to Action, ' including their relationship to the United Nations Declaration on the Rights of Indigenous Peoples."--
Chapter 8 First Nations Land Claims AgreementsSupplement 8.1: The Structure of the Indian Act: Accountability in Governance; Chapter 9 Inuit Land Claims Agreements; Part Six A Pathway Forward for Treaty First Nations; Chapter 10 The Commonwealth of Sovereign Indigenous Nations (CSIN); Chapter 11 Conclusion; Appendix A The Numbered Treaties: Making Way for the White Man; Appendix B Text of Treaty 6; References
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on March 04, 2025).
eBooks on EBSCOhost
Keywords: Indians, Treatment of -- Canada; Indigenous peoples -- Canada -- Social conditions; Indigenous peoples -- Canada -- Economic conditions; Indigenous peoples -- Canada -- Government relations; Indigenous peoples -- Civil rights -- Canada; Native peoples -- Civil rights -- Canada; Indigenous peoples -- Canada -- Claims; Peuples autochtones -- Canada -- Conditions sociales; Peuples autochtones -- Canada -- Conditions économiques.; Peuples autochtones -- Canada -- Relations avec l'État.; Autochtones -- Droits -- Canada; Peuples autochtones -- Canada -- Réclamations.; Attitudes envers les Peuples autochtones -- Canada; HISTORY -- Canada -- General; Indigenous peoples -- Social conditions; Indigenous peoples -- Government relations; Indigenous peoples -- Economic conditions; Indigenous peoples -- Civil rights; Indians, Treatment of; Canada; Soziale Situation; Indianer; Wirtschaftliche Lage; Bürgerrecht